CTC1 Mutations in a Patient with Dyskeratosis Congenita - Keller, Rachel B. (2012)
Dyskeratosis congenita (DC) is a rare inherited bone marrow failure syndrome caused by mutations in 7 genes involved in telomere biology, with approximately 50% of cases remaining genetically uncharacterized. We report a patient with classic DC carrying a compound heterozygous mutation in the CTC1 (conserved telomere maintenance component 1) gene, which has recently implicated in the pleiotropic syndrome Coats plus. This report confirms a molecular link between DC and Coats plus and expands the genotype-phenotype complexity observed in telomere-related genetic disorders.